2021
DOI: 10.1016/j.xcrm.2021.100260
|View full text |Cite
|
Sign up to set email alerts
|

A rich meconium metabolome in human infants is associated with early-life gut microbiota composition and reduced allergic sensitization

Abstract: Summary Microbiota maturation and immune development occur in parallel with, and are implicated in, allergic diseases, and research has begun to demonstrate the importance of prenatal influencers on both. Here, we investigate the meconium metabolome, a critical link between prenatal exposures and both early microbiota and immune development, to identify components of the neonatal gut niche that contribute to allergic sensitization. Our analysis reveals that newborns who develop immunoglobulin E (IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
(61 reference statements)
0
24
1
Order By: Relevance
“…WGCNA was originally applied to transcriptomics data, but it has also been recently employed for network generation using metabolomics data from human and human microbiome ( Osterhoff et al, 2014 ; Pedersen and Sofia, 2018 ; Vernocchi et al, 2020 ; Murga-Garrido et al, 2021 ; Petersen et al, 2021 ), animal ( Wu et al, 2021 ), and plants ( DiLeo et al, 2011 ). ( Samal and Martin, 2011 ).…”
Section: Experimental Networkmentioning
confidence: 99%
“…WGCNA was originally applied to transcriptomics data, but it has also been recently employed for network generation using metabolomics data from human and human microbiome ( Osterhoff et al, 2014 ; Pedersen and Sofia, 2018 ; Vernocchi et al, 2020 ; Murga-Garrido et al, 2021 ; Petersen et al, 2021 ), animal ( Wu et al, 2021 ), and plants ( DiLeo et al, 2011 ). ( Samal and Martin, 2011 ).…”
Section: Experimental Networkmentioning
confidence: 99%
“… 111 , 112 Lower relative abundances of certain bacteria (for example, Bifidobacterium, Akkermansia and Faecalibacterium), higher relative abundance of particular fungi (Candida and Rhodotorula) and a distinct fecal metabolome enriched for pro-inflammatory metabolites is a risk factor for the development of allergy. 113 Neonatal gut microbiome dysbiosis might promote the CD4+ T cell dysfunction associated with childhood atopy. 114 The onset of this mechanism might well be before birth.…”
Section: The Gastrointestinal Microbiomementioning
confidence: 99%
“… 114 The onset of this mechanism might well be before birth. 113 A greater relative abundance of Bacteroidaceae, Clostridiaceae, and Enterobacteriaceae and a lower relative concentration of Bifidobacteriaceae and Lactobacillaceae is associated with the development of allergic sensitization, eczema, or asthma. 115 In light of this, modulation of the GI microbiome is a potential preventive and therapeutic target in infants with CMA.…”
Section: The Gastrointestinal Microbiomementioning
confidence: 99%
“…The composition of gut microbiota at the age of 3-6 months was found to be associated with milk allergy by the age of 8 years with the enrichment of class Clostridia and phylum Firmicutes in the infant's gut microbiota (Bunyavanich et al, 2016). Moreover, a recent study has shown that the newborns, who developed IgE-mediated allergic sensitization by 1 year of their age, exhibited less diverse gut metabolic activities at their birth, and the specific metabolic clusters were associated with the abundance of key taxa, driving the maturation of gut microbiota (Petersen et al, 2021).…”
Section: Gut Microbiota In Early Childhoodmentioning
confidence: 99%